Fore Poppet Design and Optimization to Apply on Norway type Trawler Fishing Ships - OZHAN, Serap Dogan; ANIK, Burak Galip (International Journal of Computational and Experimental Science and Engineering, 2023)
In the classical sea landing methods of ships, aquaplaning and slipway support systems are used. In Norwegian Type Trawler Fishing vessels, the outer shell surface geometry is very delicate. Therefore; the incoming forces are extreme and the use of wooden poppets by these forces in normal sea landings is insufficient. This work; It includes two different steel fore poppet designs and analyzes for the Norwegian type trawler fishing vessel, which cannot be launched with conventional slipway support systems after landing calculations. Within the scope of this study, two different steel fore poppets were designed. After the analyzes and examinations, it was decided that the Norwegian type trawler fishing vessel, which is the subject of the article, with which steel fore poppet design will be launched without any problems. Studies carried out in this context; Two different steel fore poppet designs were made using the Rhinoceros analysis program, which is a 3D design program.Rhinoceros Scan & Solve analysis was performed and simulation was run by applying forces to the designed steel fore poppets. A force of 3e+06N, including gravity, was applied to both designed structures. As a result of this; In the first steel fore poppet structure, a maximum displacement of 1.18611mm occurred. In structures designed under a force of 3e+06N; In the first structure, the maximum Von Mises Stress value was found to be 505.761MPa. In the second structure, the maximum Von Mises Stress value was found to be 163.142MPa.